USM AND AURIGENE INDIA TO FURTHER DEVELOP COLLABORATION INITIATIVES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
BERTAM, 9 December 2016 – The Advanced Medical and Dental Institute (AMDI) of Universiti Sains Malaysia (USM) today had a reception for the delegates from Aurigene Discovery Technologies Limited India, led by its Chief Executive Officer Chavali S.N.Murthy and accompanied by 5 other officers.